A Review on the Disposal Methods with Intrinsic Environmental and Economic Impacts of Scrap Tyres in Nigeria - Francis Boluwaji Elehinafe; Yebtemiya Judith Hassan; Adewole Johnson Adesanmi; Queen Edidiong Ebong-Bassey (Automotive Experiences, 2022)
The rapid increase in the amount of tyres discarded yearly leads to the problem of scrap tyres littering the country, Nigeria thereby leading to environmental pollution. This paper looks at the extent of the menace scrap tyres has caused, the methods of their disposal and the effects on the environment. The study calls for a concerted effort from researchers, industry operators and regulatory bodies to be up and doing in the disposal of scrap tyres in Nigeria to check the degradation of the environment in its three compartments: air, water and land, with a view to upholding environmental sustainability and embedded economic advantages.